2017
DOI: 10.1007/s40858-017-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Technologies for the detection of Fusarium head blight disease and airborne inoculum

Abstract: Many pathogens are dispersed by airborne spores, which can vary in space and time. We can use air sampling integrated with suitable diagnostic methods to give a rapid warning of inoculum presence to improve the timing of control options, such as fungicides. Air sampling can also be used to monitor changes in genetic traits of pathogen populations such as the race structure or frequency of fungicide resistance. Although some image-analysis methods are possible to identify spores, in many cases, species-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Similar predictive models should be developed for other countries facing wheat blast outbreaks, including Bolivia, Paraguay, Bangladesh and India. The major advantage of using a model like Sisalert based on the automated collection of weather data is to provide a warning of an imminent risk of wheat blast infection (West et al ., ; West and Kimber, ). This alert enables real‐time decision‐making for fungicide applications.…”
Section: Strategies For the Management Of Wheat Blastmentioning
confidence: 98%
“…Similar predictive models should be developed for other countries facing wheat blast outbreaks, including Bolivia, Paraguay, Bangladesh and India. The major advantage of using a model like Sisalert based on the automated collection of weather data is to provide a warning of an imminent risk of wheat blast infection (West et al ., ; West and Kimber, ). This alert enables real‐time decision‐making for fungicide applications.…”
Section: Strategies For the Management Of Wheat Blastmentioning
confidence: 98%
“…However, multispectral and RGB imagery are used to detect only infected ears with typical symptoms via sophisticated analysis of the image under uniform illumination conditions. Spectroscopy and imaging platforms for tractors, UAVs, aircraft and satellites are current innovative technologies for mapping disease in wild fields [16].…”
Section: Introductionmentioning
confidence: 99%
“…RDVI and OSAVI were both established to improve the sensitivity of NDVI to soil backgrounds [20]. The good performances of these indices indicated that even if FHB occurred at the flowering stage (Feekes 10.5) through to the milk-ripening stage (Feekes 11.1) [50], soil background still had an effect on the canopy spectral reflectance. The red-edge VIs, i.e., NREDI1, NREDI2, and NREDI3, were modifications of NDVI with red-edge1, red-edge2, and red-edge3, respectively, and the R 2 of models developed from these indices were 0.46, 0.42, and 0.21 respectively.…”
Section: Discussionmentioning
confidence: 99%